Relationship Between Early Breastfeeding Complementary Foods and Mother's Knowledge of Toddler Nutrition with Stunting Incidence at the Ikur Koto Community Health Center, Padang City - Lisma Evareny; Sri Wahyuni; Endrinaldi (POLTEKKES KEMENKES PADANG, 2023)
Background: Stunting (short body) is long-term outcomes of nutrient deficiencies with height according to age less than -2 SD (Standard Deviation) below the median length. Which has an impact on motor and sensory developmental disorders and decreased quality of life. The purpose of this study was to determine the relationship of early breastfeeding supplementation and the level of maternal knowledge about nutrition of toddlers aged 24-36 months to stunting at the Ikur Koto Community Health Center, Padang City. Methods: This research is a quantitative study withdesign cross sectional, carried out in the work area of the Ikur Koto Community Health Center from January 2019 to August 2019. The sample in this study was mothers who had children aged 24-36 months as many as 80 people. Mothers as respondents were interviewed directly using a questionnaire. The incidence of stunting in children is measured by TB / U indicators and interpreted with software WHO-anthro. Univariate and bivariate data analysis using analysis chi-square (p≤0.05). The results showed the percentage of stunting was 42.5%. The results of bivariate analysis showed that there was a relationship between early MP-ASI (p = 0.001; OR =8,680; Cl =2,320- 32,476) and maternal nutritional knowledge (p = 0.001; OR =23,864; Cl = 6,879-82,789) with stunting in children. age 24-36 months. Conclusion: There is a significant relationship between early breastfeeding supplementary nutrition and maternal nutrition knowledge and the incidence of stunting in children aged 24-36 months. Suggestions: It is expected that efforts to prevent stunting focused in the first 1000 days of life are preventive efforts in detecting stunting events.